2020
DOI: 10.3889/oamjms.2020.5345
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mutagenesis and Cytogenetic Chromosomal Abnormalities in a Population Living in the Aral Sea region

Abstract: AIM: The article presents the results of a study of chromosomal mutations in residents living in the Aral Sea disaster zone, using the example of the city of Aralsk. METHODS: The article identifies the level of chromosomal aberrations (CA) in the surveyed population and identifies the leading type of aberrations in this region. RESULTS: Researches have shown that the main types of structural changes were chromatid breaks and single fragments of chromosomes. The results showed that in the study popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previously, an increased CA frequency among females in B&H was reported (Nefić and Mušanović, 2014;Mačkić-Đurović et al, 2017), and the values were also higher compared to the background level of CA in the population of Croatia (Rozgaj and 2008). Generally, the level of chromosome aberrations may differ between the countries and this could be attributed to lifestyle differences, geographical location, weather conditions, and pollution levels across Europe that could affect the frequencies of such parameters (Sierra-Torres et al, 2004;Sabirov et al, 2020;Musilova et al, 2023). On the contrary, certain lifestyle factors have beneficial effects in maintaining genomic integrity (Fenech et al, 2023;Santovito et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, an increased CA frequency among females in B&H was reported (Nefić and Mušanović, 2014;Mačkić-Đurović et al, 2017), and the values were also higher compared to the background level of CA in the population of Croatia (Rozgaj and 2008). Generally, the level of chromosome aberrations may differ between the countries and this could be attributed to lifestyle differences, geographical location, weather conditions, and pollution levels across Europe that could affect the frequencies of such parameters (Sierra-Torres et al, 2004;Sabirov et al, 2020;Musilova et al, 2023). On the contrary, certain lifestyle factors have beneficial effects in maintaining genomic integrity (Fenech et al, 2023;Santovito et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…It can be the change in the structure of morbidity, prolonged and chronic course of diseases in all age groups, the course of diseases in atypical forms and manifestations, the increase in morbidity and inhibition of immunological reactivity of the organism, the growth of oncological morbidity, the chronization of pathologies of all organs, and systems [6]. Moreover, Sabirov et al demonstrated the effect of chemical pollution to the chromosomal mutagenesis in the region of the Aral Sea [8]. Also, a correlation is found that people from the pre-Aral region have the highest frequency of digestive system diseases in Kazakhstan due to high level of pollutant in the water [9].…”
Section: Introductionmentioning
confidence: 99%